Identifying the sister group to the bees: a molecular phylogeny of Aculeata with an emphasis on the superfamily Apoidea - Andrew H. Debevec; Sophie Cardinal; Bryan N. Danforth (Zoologica Scripta, 2012)
Debevec, AH., Cardinal, S & Danforth, BN. Identifying the sister group to the bees: a molecular phylogeny of Aculeata with an emphasis on the superfamily Apoidea. — Zoologica Scripta , 41 , 527–535. The hymenopteran superfamily Apoidea includes the bees (Anthophila) as well as four predatory wasp families (Heterogynaidae, Ampulicidae, Sphecidae and Crabronidae) collectively referred to as the “sphecoid” or “apoid” wasps. The most widely cited studies suggest that bees are sister to the wasp family Crabronidae, but alternative hypotheses have been proposed based on both morphological and molecular data. We combined DNA sequence data from previously published studies and newly generated data for four nuclear genes (28S, long‐wavelength rhodopsin, elongation factor‐1α and wingless ) to identify the likely sister group to the bees. Analysis of our four‐gene data set by maximum likelihood and Bayesian methods indicates that bees most likely arise from within a paraphyletic Crabronidae. Possible sister groups to the bees include Philanthinae, Pemphredoninae or Philanthinae + Pemphredoninae. We used Bayesian methods to explore the robustness of our results. Bayes Factor tests strongly rejected the hypotheses of crabronid monophyly as well as placement of Heterogynaidae within Crabronidae. Our results were also stable to alternative rootings of the bees. These findings provide additional support for the hypothesis that bees arise from within Crabronidae, rather than being sister to Crabronidae, thus altering our understanding of bee ancestry and evolutionary history.